2022
DOI: 10.1002/mpr.1938
|View full text |Cite
|
Sign up to set email alerts
|

Association between mental health and academic performance among university undergraduates: The interacting role of lifestyle behaviors

Abstract: Objectives Impaired mental health status tends to be associated with poor academic performance, but few prospective studies have examined the association between mental health and academic performance among undergraduates while considering the interacting roles of multiple lifestyle behaviors. Participants and Methods A total of 1823 Japanese undergraduate students (67% men) were followed up for 4 years. Their mental health status was measured by the six‐item Kessler Psychological Distress Scale (K6). We defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…Third, the definition of poor AP in this study might not be applicable in different faculties or at other universities. Finally, it should be noted that mental health factors that this study did not include, but we already confirmed the association between mental health and academic performance in the other study [23]. Cumulative incidence rate, %…”
Section: Discussionsupporting
confidence: 72%
“…Third, the definition of poor AP in this study might not be applicable in different faculties or at other universities. Finally, it should be noted that mental health factors that this study did not include, but we already confirmed the association between mental health and academic performance in the other study [23]. Cumulative incidence rate, %…”
Section: Discussionsupporting
confidence: 72%
“…Dabei wurden 95 % der Studierenden vor Beginn des Studiums als "frei von depressiver Symptomatik" eingestuft, während es nach 2 Jahren nur noch 87 % der Medizinstudierenden waren [40]. Weitere Ergebnisse deuten darauf hin, dass die psychische Gesundheitzu Beginndes Studiums einPrädiktor für den weiteren Studienverlauf ist [8]. Demnach ist die Studieneingangsphase von hoher Bedeutung für eine frühe Gesundheitsförderung und Prävention hinsichtlich fortschreitender Studienbelastungen.…”
Section: Hintergrundunclassified
“…While cognitive metrics like GPA and standardized test scores have traditionally been the focus of academic success predictors, recent scholarship has illuminated the critical role of non-cognitive factors. Psychological well-being, societal influences, and lifestyle habits are increasingly recognized as pivotal to shaping academic outcomes, prompting a shift towards a more holistic understanding of academic performance (Alhajraf & Alasfour, 2014;Al-Khani, Sarhandi, Zaghloul, Ewid & Saquib, 2019;Chu, Liu, Takayanagi, Matsushita & Kishimoto, 2023;Nawa, Numasawa, Nakagawa, Sunaga, Fujiwara, Tanaka et al, 2020;Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%